Cell type-specific delivery of short interfering RNAs by dye-functionalised theranostic nanoparticles - Press, Adrian T.; Traeger, Anja; Pietsch, Christian; Mosig, Alexander; Wagner, Michael; Clemens, Mark G.; Jbeily, Nayla; Koch, Nicole; Gottschaldt, Michael; Beziere, Nicolas; Ermolayev, Volodymyr; Ntziachristos, Vasilis; et al. (Nature Communications, 2014)
Efficient delivery of short interfering RNAs reflects a prerequisite for the development of RNA interference therapeutics. Here, we describe highly specific nanoparticles, based on near infrared fluorescent polymethine dye-derived targeting moieties coupled to biodegradable polymers. The fluorescent dye, even when coupled to a nanoparticle, mimics a ligand for hepatic parenchymal uptake transporters resulting in hepatobiliary clearance of approximately 95% of the dye within 45 €‰min. Body distribution, hepatocyte uptake and excretion into bile of the dye itself, or dye-coupled nanoparticles can be tracked by intravital microscopy or even non-invasively by multispectral optoacoustic tomography. Efficacy of delivery is demonstrated in vivo using 3-hydroxy-3-methyl-glutaryl-CoA reductase siRNA as an active payload resulting in a reduction of plasma cholesterol levels if siRNA was formulated into dye-functionalised nanoparticles. This suggests that organ-selective uptake of a near infrared dye can be efficiently transferred to theranostic nanoparticles allowing novel possibilities for personalised silencing of disease-associated genes.
CRIS-Team Scopus Importer:2023-03-08